Penguatan UMKM Desa Binaan Berbasis SDGs Digital di Santanamekar - Purwaamijaya, Btari Mariska; Nugraha, Muhammad Rizki; Maesaroh, Syti Sarah; Ar-Ridlo, Muhammad Dzikri; Prehanto, Adi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service project is a program aimed at strengthening Micro, Small, and Medium Enterprises (MSMEs) in Santanamekar Village, designed based on the principles of digital Sustainable Development Goals (SDGs). The program aims to enhance the capacity and competitiveness of local MSMEs by providing comprehensive training in digital marketing, attractive product packaging, and understanding legal aspects of business operations. Through a participatory methodology, MSME actors are actively involved in every stage of the training, which fosters a sense of ownership and improves the success of program implementation. The results of the training show a significant increase in the confidence of MSME actors as well as their skills in applying digital marketing strategies and improving product quality. By leveraging digital technology, this program has the potential to open wider market access and increase the visibility of MSME products in the online realm. Additionally, support in packaging and understanding the legal aspects related to business provides a solid foundation for MSMEs to operate legally and efficiently. Overall, this program not only contributes to local economic growth but also plays a role in creating a more sustainable business environment. This program recommends the need for ongoing training and sustained support for MSMEs in Santanamekar Village to face increasingly complex challenges in the global market.